2020
DOI: 10.1080/10643389.2020.1795053
|View full text |Cite
|
Sign up to set email alerts
|

The roles of membrane transporters in arsenic uptake, translocation and detoxification in plants

Abstract: Arsenic (As) is one of the most toxic environmental contaminants that is ubiquitously distributed in the environment. Millions of people worldwide suffer from As poisoning due to As exposure from drinking water and dietary intake. Reducing As accumulation in food crops is of great importance for food safety and public health. Limiting As accumulation in food crops or phytoremediation of Ascontaminated soil depend on a detailed understanding of As uptake and transport in plants. Plants take up and transport dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 175 publications
(263 reference statements)
1
32
1
Order By: Relevance
“…Plant mineral transporters are critical for the accumulation and detoxification of heavy metal metals and metalloids through uptake, xylem/phloem loading and unloading, as well as sequestration (Sharma et al, 2020;Zhao and Wang, 2020;Deng et al, 2021). Various toxic metal transporters in distinct families have been identified and characterized during the last few decades (Che et al, 2018;Tang and Zhao, 2021). Recently, it has been revealed that jasmonates coordinate the transport systems of the toxic minerals to restrict accumulation and enhance tolerance (Lei et al, 2020b;Mousavi et al, 2020;Verma et al, 2020).…”
Section: Ja Signaling Pathways In Response To Toxic Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant mineral transporters are critical for the accumulation and detoxification of heavy metal metals and metalloids through uptake, xylem/phloem loading and unloading, as well as sequestration (Sharma et al, 2020;Zhao and Wang, 2020;Deng et al, 2021). Various toxic metal transporters in distinct families have been identified and characterized during the last few decades (Che et al, 2018;Tang and Zhao, 2021). Recently, it has been revealed that jasmonates coordinate the transport systems of the toxic minerals to restrict accumulation and enhance tolerance (Lei et al, 2020b;Mousavi et al, 2020;Verma et al, 2020).…”
Section: Ja Signaling Pathways In Response To Toxic Elementsmentioning
confidence: 99%
“…Plant response to heavy metals and metalloids should be integrated into breeding programs to optimize their growth, development, and metabolism for survival. Although large number of functional proteins involved in the accumulation and detoxification of toxic elements have been identified (Clemens and Ma, 2016;Lindsay and Maathuis, 2017;Lei et al, 2020a;Sharma et al, 2020;Zhao and Wang, 2020;Tang and Zhao, 2021), the signal transmission from mineral stress sensing to the regulation of downstream genes is less known. Regulatory models at molecular levels in various plant species have been proposed based on the systematic transcriptomic and biochemical FIGURE 3 | Jasmonic acids limit the accumulation and enhance the tolerance to the toxic elements by coordinating the transport system, activity of antioxidant enzymes, and chelating capacity in plants.…”
Section: Regulatory Components Of Ja-responsive Signaling Pathways In Response To Toxic Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, we might look to the As(III)-transport literature to shed some light. Indeed, OsLsi2 has been demonstrated to be capable of As(III) transport and a crucial component of the xylem-loading process ), but other transporters have been identified in pericycle and xylem parenchyma cells, including a C-type ATP-binding cassette (ABC) transporter, OsABCC7, which plays a more direct role in xylem loading and root-to-shoot translocation of As(III) (Tang et al 2019;Tang and Zhao 2020). It is still unknown if such mechanisms exist for Si.…”
Section: Lsi2 Is Responsible For Xylem Loading and Tissue Si Contentmentioning
confidence: 99%
“…Over-expression of TaZnF in A. thaliana significantly increased tolerance to heat and cold stress as well as promotes early flowering [16]. Similarly, there are numerous studied in many plant species evidenced the pivotal role of MTs in uptake, sequestration, translocation and detoxification of toxic HMs including cadmium (Cd) [17], chromium (Cr) [18], lead (Pb) [19], As [20], cobalt (Co) and zinc (Zn) [21], for more detail see section 3.…”
Section: Introductionmentioning
confidence: 99%